DAWN RAIDS AND (DIS)PROPORTIONALITY BETWEEN THE POWERS AND OBLIGATIONS OF THE COMMISSION FOR PROTECTION OF COMPETITION - Begović, Boris; Ilić, Nikola (Pravni zapisi, 2022)
If there is a reasonable suspicion that evidence of competition law infringement may be destroyed or altered, the Commission for Protection of Competition (CPC) is authorized to inspect market participants’ premises, without prior notice or any court order or even an effective ex-post court control. Such an investigation may disrupt the market participants’ activities and reduce their competitiveness, which is contrary to the key goals of the competition law. This paper analyzes sources of law for the unannounced investigation in the European Union (EU) competition law and Serbian law, as well as the practice of conducting unannounced investigations in EU member states and Serbia. Based on the findings, the conclusion is that Serbia should adopt, among others, amendments to the Law on Protection of Competition, and regulation defining CPC's powers and obligations, so that any differences in CPC’s conduct in the same or similar cases are decreased through uniform application of competition law, competition is effectively protected and legal uncertainty for market participants, which is currently significantly higher than in the EU member states, is reduced.
Keywords: competition law; dawn raid; Commission for Protection of Competition; legal certainty; law enforcement